ADHERENCE OF HEMODIALYSIS PATIENTS WITH CHRONIC RENAL FAILURE TO TREATMENT GUIDELINES - Eva Nandawati; Marlina; Marthoenis (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Background: End-stage renal Disease (ESRD) is a major health problem for most people, with a large burden on healthcare systems and economies around the world. This disease requires various medical treatments in the form of hemodialysis, peritoneal dialysis, or hemofiltration. The duration of treatment depends on the cause and extent of kidney damage; this will be more dangerous if the sufferer is not dialysis or transplanting the kidney. Methods: This cross-sectional study was conducted among 176 patients with end-stage chronic renal failure who underwent hemodialysis and were selected by purposive sampling. Data were collected using a patient perception questionnaire, a Multidimensional Scale of Perceived Social Support (MSPSS) questionnaire, and an end-stage renal disease adherence questionnaire (ESRD-AQ). Data were analyzed using frequency distribution, chi-square test, and binary logistic regression. Results: This study showed that the results of long hemodialysis (HD) (P = 0.000), long-suffering from ERDS (P = 0.000), social support (P = 0.006), perception of nurse services (P = 0.038) and availability of transportation (P = 0.031) were associated with compliance of CKD patients with hemodialysis. Duration of hemodialysis (HD) (P = 0.000; OR = 8.597) was the most dominant factor associated with compliance of CKD patients on hemodialysis. Conclusion: The length of hemodialysis (HD) is the most dominant factor associated with the adherence of CRF patients undergoing hemodialysis, where the length of HD can be a factor that affects a person's compliance with CRF when undergoing hemodialysis. In certain circumstances, long HD can be a reminder for someone to remember to undergo hemodialysis so that metabolic waste does not accumulate in the patient's body.